Optimization of in vitro carbohydrate digestion by mammalian mucosal α-glucosidases and its applications to hydrolyze the various sources of starches. (February 2019) - Shin, Hansol; Seo, Dong-Ho; Seo, Jungmin; Lamothe, Lisa M.; Yoo, Sang-Ho; Lee, Byung-Hoo
Abstract: Glycemic carbohydrates, such as starch and sucrose, are fully hydrolyzed into monosaccharides by mucosal α-glucosidases in the small intestine. In this study, we optimized the reaction conditions of mammalian mucosal α-glucosidases to digest various types of glycemic carbohydrates to determine their hydrolytic activity. The results clearly showed that mammalian mucosal α-glucosidases had different hydrolytic properties compared to fungal amyloglucosidase, which is commonly used in vitro assay to determine carbohydrate quality, on various sizes and α-linked carbohydrates. Furthermore, non-gelatinized and gelatinized starches from different botanical sources were differently hydrolyzed to glucose by the prepared solution of mammalian α-glucosidases and porcine pancreatic α-amylase. Thus, it is clearly suggested that the digestion of glycemic carbohydrates by the optimized reaction condition with mammalian mucosal α-glucosidases and pancreatic α-amylase can be applied to determine the carbohydrate quality and digestion properties as it is more reliable to human digestive enzymes compared to fungal or microbial α-glucosidases. Graphical abstract: Image 1 Highlights: Glycemic carbohydrate digestions by mammalian α-glucosidases were optimized. Pancreatic α-amylase assists α-glucosidase activity during carbohydrate digestion. Novel approach to determine the glycemic carbohydrate quality and digestibility.